2015
DOI: 10.1039/c4cc10395e
|View full text |Cite
|
Sign up to set email alerts
|

Isotope sensitive branching and kinetic isotope effects to analyse multiproduct terpenoid synthases from Zea mays

Abstract: Multiproduct terpene synthases TPS4-B73 and TPS5-Delprim from Zea mays exhibit isotopically sensitive branching in the formation of mono- and sesquiterpene volatiles. The impact of the kinetic isotope effects and the stabilization of the reactive intermediates by hyperconjugation along with the shift of products from alkenes to alcohols are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…13,16 Here, we describe the effects of substrate's conformation on the initial cyclization and the further course of individual protonation and deprotonation reactions by means of deuterium labeling. In contrast to our previous study, 14 both TPS4 and TPS5 cyclize labeled (2Z,6E)-FDP (2cd) and (2Z)-GDP (2a-b) showed quantitative difference in volatile composition as compared to natural substrates. Interestingly, they exhibited much higher turnover with (2Z) substrates (2a-d) than with their natural (2E) substrates (1ad) and a reduced ratio of acyclic to cyclic products.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…13,16 Here, we describe the effects of substrate's conformation on the initial cyclization and the further course of individual protonation and deprotonation reactions by means of deuterium labeling. In contrast to our previous study, 14 both TPS4 and TPS5 cyclize labeled (2Z,6E)-FDP (2cd) and (2Z)-GDP (2a-b) showed quantitative difference in volatile composition as compared to natural substrates. Interestingly, they exhibited much higher turnover with (2Z) substrates (2a-d) than with their natural (2E) substrates (1ad) and a reduced ratio of acyclic to cyclic products.…”
Section: Introductioncontrasting
confidence: 99%
“…13 We have recently reported about the kinetic isotope effects and enhanced formation of alcohols over olefinic products by deuterated precursors of (2E)-GDP and (2E,6E)-FDP as compared to natural substrates. 14 To reveal further details of the enzyme mechanism, we synthesized geranyl-and farnesyl diphosphates including both geometric isomers of the critical C(2)-C(3) bond (Scheme 1) using deuterium labels as a probe for isotope sensitive branching. We were interested in whether the cyclization of cis-isomers (2Z)-GDP (2a-b) and (2Z,6E) FDP (2c-d) would proceed via the same cascade as observed with their corresponding trans-substrates (1a-d) (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…of isotopically sensitive branching of product formation in maize supports the enzymatic biosynthesis of mono-and sesquiterpene volatiles from a shared carbocationic precursor for branched cascade in multiproduct synthases. 100,101 TPS4 and TPS5 from Zea mays showed major turnover enhancements with isomers as substrates although with the similar product profile as compared with natural substrates. 100 However, the examination of MtTPS5 enzyme from Medicago truncatula for substrate promiscuity with (Z,E)-FDP showed massive variations in product profile.…”
Section: Substrate Isomersmentioning
confidence: 92%
“…Thermochemical parameters calculated at the B3LYP/6‐311++G(d,p) model showed that the carboxyl group (PA = 216.1 kcal/mol) of 3 is the most reactive site to the proton attachment (Figure ), followed by the prenyl (PA = 209.0 kcal/mol) and the pyran subunits (PA = 205.5 kcal/mol). Under CID‐MS/MS conditions, the lower energy barrier for proton transfer between the acyl and prenyl subunits (for instance, ∆PA = 7.1 kcal/mol) is due to the formation of a tertiary carbocation, which results in the most stable ion . In this case, hyperconjugative interaction between C─H and C─C σ bonds and the empty π* orbital on the cationic center makes substantial contributions to the charge stabilization of protonated 2 H ‐chromene 3 .…”
Section: Resultsmentioning
confidence: 99%
“…19,25,52 The fragmentation pathway proposed for the m/z 203 ion generated from the [1 + H] + can also be extended to the m/z 255 ion the formation of a tertiary carbocation, which results in the most stable ion. 46,53,54 In this case, hyperconjugative interaction between C─H and C─C σ bonds and the empty π* orbital on the cationic center makes substantial contributions to the charge stabilization 46,53,54 of protonated 2H-chromene 3.…”
Section: Protonation Sitesmentioning
confidence: 99%